1975
DOI: 10.1136/jcp.28.10.828
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance and source of lactate dehydrogenase and its isoenzymes in cerebrospinal fluid of children with a variety of neurological disorders.

Abstract: Two hundred and thirty-four cerebrospinal fluid (CSF) specimens from 183 different children were analysed for total lactate dehydrogenase (LD) activity and LD isoenzyme distribution. The LD activities were elevated in the CSF of patients with meningitis, especially with bacterial infections, and with central nervous system (CNS) leukaemia. The CSF LD isoenzyme patterns of both groups generally reflected the number and distribution of lymphocytes and granulocytes in the CSF. Increases in CSF LD levels also occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The LDH activity in CSF in PM is significantly higher (p <0.005) than in TBM. The LDH isoenzyme studies carried out in cases of bacterial meningitis have shown that the isoenzyme pattern is primarily a reflection of the presence or absence of leukocytes, and of the predominant type of cell present [18]. Although the number of cases studied in our case was relatively small, it is believed that it has significant value in diagnosis of early meningitis.…”
Section: Observationmentioning
confidence: 87%
“…The LDH activity in CSF in PM is significantly higher (p <0.005) than in TBM. The LDH isoenzyme studies carried out in cases of bacterial meningitis have shown that the isoenzyme pattern is primarily a reflection of the presence or absence of leukocytes, and of the predominant type of cell present [18]. Although the number of cases studied in our case was relatively small, it is believed that it has significant value in diagnosis of early meningitis.…”
Section: Observationmentioning
confidence: 87%
“…The CSF total LDH and its isoenzymes LDH-1, LDH-2 and LDH-3 apparently originate from brain tissue, which contains the same isoenzymes (2,5,10). All levels increase when brain tissue is damaged as a result of non-infectious neurological disorders such as hydrocephalus, brain tumours and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al (5) described the LDH activity in the CSF with non-specific febrile convulsions. However, there are no published analyses of LDH isoenzymes in febrile seizures.…”
mentioning
confidence: 99%
“…These include: bacterial meningitis (increase in LDH-4 and LDH-5); viral meningitis (increase in LDH-1 and LDH-2); intracranial tumors (LDH-5): cerebral hemorrhage (LDH-3, LDH-4, and LDH-5); leukemic and lymphomatous infiltration (LDH-3 and LDH-4); tuberculous meningitis (LDH-3); hydrocephalus (LDH-2 and LDH-3), and Guillain-Barré syndrome (LDH-3) [8, 9, 10, 11]. Some authors have suggested a disturbance in the blood-brain barrier which enables plasma LDH to reach the CSF, or alternatively, LDH production by neoplastic tissue or white blood cells and exogenous bacterial sources [4, 8, 12, 13, 14]. However, neither hypothesis has yet been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Theories include a dysfunction of the monoaminergic neurotransmitter system in the brain stem and an abnormality of the immune system [1, 2]. CSF LDH and its typical isoenzymes, LDH-1, LDH-2, and LDH-3, apparently originate from the brain tissue which contains the same isoenzymes [13, 14]. Damage to the brain tissue in neurological non-infectious situations such as epilepsy or brain tumor causes an elevation in the total CSF LDH and the brain tissue isoenzymes, LDH-1 to LDH-3 [14].…”
Section: Discussionmentioning
confidence: 99%